Nutritional Requirements for Reproduction of Micromus tasmaniae Walker - Hussein, Mohd Yusof (1984)
A laboratory experiment was conducted to determine whether it is males or females of Micromus tasmaniae Walker that require nutrients other than sugar to mate and promote egg development. Four categories of diets were tested on newly emerged adults. The treatments were differentiated based on whether or not male or female or both sexes were deprived of live prey (Myzue persicae Sulzer) before pa~ring. Egg. counts indicated that opposition occurred mainly when females had access to aphids prior to pairing. Depriwing the males of aphids did not alter the incidence of oviposition. It is necessary to provide females with live aphids prior to mating to be able to rear them.